FIGO good practice recommendations on cervical cerclage for prevention of preterm birth. Issue 1 (14th September 2021) - Shennan, Andrew; Story, Lisa; Jacobsson, Bo; Grobman, William A.; ,
Abstract: Cervical cerclage is an intervention which when given to the right women can prevent preterm birth and second‐trimester fetal losses. A history‐indicated cerclage should be offered to women who have had three or more preterm deliveries and/or mid‐trimester losses. An ultrasound‐indicated cerclage should be offered to women with a cervical length <25 mm if they have had one or more spontaneous preterm birth and/or mid‐trimester loss. In high‐risk women who have not had a previous mid‐trimester loss or preterm birth, an ultrasound‐indicated cerclage does not have a clear benefit in women with a short cervix. However, for twins, the advantage seems more likely at shorter cervical lengths (<15 mm). In women who present with exposed membranes prolapsing through the cervical os, a rescue cerclage can be considered on an individual case basis, taking into account the high risk of infective morbidity to mother and baby. An abdominal cerclage can be offered in women who have had a failed cerclage (delivery before 28 weeks after a history or ultrasound‐indicated [but not rescue] cerclage). If preterm birth has not occurred, removal is considered at 36–37 weeks in women anticipating a vaginal delivery. Synopsis: Cervical cerclage given to the right women can prevent preterm birth and second‐trimester fetal losses.